Pesquisadores da área da saúde e ética nas pesquisas com crianças e adolescentes: um estudo em Minas Gerais - Nadia Veronica Halboth (2014)
Health research with children and adolescents is necessary for the development of science, aiming to produce new knowledge, therapeutic procedures and the welfare of these subjects, but some ethical peculiarities need to be considered for its achievement. Although the use of such subjects in research has a long history, the ethical care of children and adolescents has not always met their specificities. This thesis aimed to understand how, in the current moment when children and adolescents rights are being strengthened and the dimension of equity and equal care for culturally diverse people is reinforced, health investigators deal with ethics in research involving the above mentioned subjects. It sought to understand researchers social representations on the ethical aspects they observe when conducting their scientific investigations. Considering that the ethical devices can be reinterpreted in practice, "adjustments" of ethical principles in the course ofinvestigations made by the researchers were searched. The historical review of research ethics in Brazil, which was also performed, showed that, as in other countries, ethical misconduct occurred here. Data analysis showed that the concern about ethical issues is often restricted to the Informed Consent, considered the main ethical aspect of scientific investigation, and that the most important motivation for developing a research project was not the value it could have for society, but the interest in having scientific papers published. The importance of research ethics boards as organs that protect research participants, especially as subjects, as well as investigators dissatisfaction with them, was evident. Although there were concerns about proper communication with research subjects and their guardians, the vulnerability of families seems notto have been protected and the condition of vulnerability of children and adolescents as research subjects was not properly valued. Finally, it seems that the educational role of research ethics boards is not being performed satisfactorily. This could change the observed reality, which isessential, so that the needed research involving children and adolescents can be developed, without violating ethical principles.